The Impact of Empowerment of the Maju Horas Farmer Group on the Economic Welfare of the Community in Huta Bosar Bayu Village, Huta Bayu Raja District, Simalungun District. - Agus Marito Saragi; Robert Sitio; Elvri Teresia Simbolon; Rusmauli Simbolon; Tio R. J Nadeak (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2025)
Empowerment can be interpreted as an effort to increase the ability of the community to participate, negotiate, influence and control the institutions of their community on a large scale for the sake of improving their lives. Describe the impact of empowerment of the Bosar Bayu Farmer group in improving community welfare. In this study, the researcher used a qualitative research type with a descriptive approach. Qualitative research is research that intends to understand the phenomenon of what is experienced by the research subject, for example behavior, perception, motivation, actions, and others holistically and by means of description in the form of words and language. The reason for choosing the type of qualitative research with a descriptive method is because the process of formulating the problem carried out in the study was carried out comprehensively, broadly, and in depth in discussing the phenomena that occurred in the field. Then the data obtained from farmers in the form of information both verbally and in writing that describes the situation directly in the field, so that it is able to describe what happened at the research location in more detail, and try to obtain and reveal data on the impact of empowerment of the Maju Horas farmer group in improving community welfare in Bosar Bayu village. Building Farmers' Knowledge and Skills, Increasing agricultural production, Increasing the standard of living and equalizing income levels, As a means of cooperation between group members. Based on the results of the research that has been discussed regarding the empowerment of the Maju Horas farmer group in improving the welfare of the community in Bosar Bayu Village, it can be concluded that empowerment is an effort to make the community independent. Keywords: Jeremiah 22:10-12, Disobedience, Exile, Leadership, Obedience to God, God's Judgment, King Shallum (Jehoahaz), Spiritual Destruction, Divine Justice, Social Suffering, Promised Land, Consequences of Disobedience, Hermeneutics, Judah's Kings, Spiritual and Political: Consequences.